Diferenças nas características físicas de ovos produzidos sob pastejo livre e sistema convencional - Galvão, Julia Arantes (2017)
The aim of this work was determine if there is differences on physical internal and external parameters of eggs produced under federal inspection at two housing systems (free range and conventional) and if the change of conventional systems for free range considering these characteristics is justified. Eggs from a free range and a conventional system were evaluated for weight, egg specific gravity, shell thickness, weight of shell/area surface, shell breaking strength, yolk percent, albumen percent, color yolk and Haugh unit. The systems where localized at the same farm, reducing introduce vies for macro climatic temperature, lineage and, in parts, of feeding. There collected samples by four cycles of 28 days. At each, there were tree collect days of 30 eggs at each system, totalizing 360 eggs by system. We observed that the weight of free-range eggs were lighter than conventional system eggs, otherwise both graded as extra type. The egg specific gravity at free-range were lowest than conventional system eggs (P < 0,001). The free-range eggs exhibited the thickest (P < 0,05) and resistant (P=0,22) eggshell, nevertheless the lighter (P < 0,05) eggshell. The albumen percent were bigger at free-range system (P < 0,05), with the yolk percent on the inverse (P < 0,05). The color yolk was intriguingly similar for both systems (P=0,56). All the evaluated eggs were AA for Haugh unit (P=0,60). Accordingly, it was demonstrated that at the evaluated farms there were differences on physical internal and external parameters of eggs (free-range and conventional system), although these differences unfounded the change of conventional systems for free-range. Additionally, we advise to add the egg yolk evaluation in loco at each farm in inspection routine.